2020
DOI: 10.3389/fpsyg.2020.571943
|View full text |Cite
|
Sign up to set email alerts
|

Bullying and Substance Use in Early Adolescence: Investigating the Longitudinal and Reciprocal Effects Over 3 Years Using the Random Intercept Cross-Lagged Panel Model

Abstract: Bullying and substance use among adolescents have been increasingly studied in the field of developmental psychology, but research to date has primarily investigated the cross-sectional relationship and, to a lesser extent, the long-term impact of bullying on substance use. Grounded in the General Theory of Crime, this study focused on the longitudinal reciprocal relationships between bullying and substance use (i.e., smoking and alcohol consumption) during early to mid-adolescence, which is a critical develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(23 citation statements)
references
References 66 publications
3
20
0
Order By: Relevance
“…This study's findings also support that CB perpetration is associated with parenting styles, which is consistent with other bullying studies. In particular, recent research [ 32 ] has reported that negative parenting (especially parenting styles related to high levels of control or punishment) increases the likelihood of adolescents developing externalized and aggressive behaviors, consistent with the findings of this study. In China and within Asian society in general, parenting styles, which include practices such as high levels of monitoring and support, seem to be better at mitigating adolescent aggression than other cultural contexts.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…This study's findings also support that CB perpetration is associated with parenting styles, which is consistent with other bullying studies. In particular, recent research [ 32 ] has reported that negative parenting (especially parenting styles related to high levels of control or punishment) increases the likelihood of adolescents developing externalized and aggressive behaviors, consistent with the findings of this study. In China and within Asian society in general, parenting styles, which include practices such as high levels of monitoring and support, seem to be better at mitigating adolescent aggression than other cultural contexts.…”
Section: Discussionsupporting
confidence: 92%
“…[ 21 ] The students who reported living with neither parent may have had a poor family self-concept and experienced communication problems frequently with their parents, leading to a more depressive mood, feelings of loneliness, and fewer socio-emotional skills, increasing their risk of impulsiveness and victimization during social networking. [ 32 ] Lu et al [ 33 ] found that students who experienced family violence might be predictive of bullying perpetration. One theoretical explanation for the link between witnessing violence and bullying perpetration in adolescence is a social learning theory, which posits that youths model behavior from others.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations